ANALYSIS OF THE EFFECT OF EXCHANGE RATE, INFLATION RATE, AND INTEREST RATE ON INDONESIA'S TEXTILE EXPORT VOLUME TO THE UNITED STATES - I Putu Gede Okan Bhaskara Muryananda; Ni Ketut Budiningsih (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the effect of the exchange rate, inflation rate, and interest rate on Indonesia's textile export volume to the United States during the quarterly period from 2015 to 2024. The selection of variables is based on the significant role of macroeconomic factors in national export performance, particularly in the textile sector, which is one of Indonesia's leading non-oil and gas export commodities. The analytical method employed is multiple linear regression to test the relationship between these variables and textile export volume. The findings reveal that the exchange rate has a positive and significant effect on Indonesia's textile exports to the United States, indicating that rupiah depreciation encourages textile export growth. Inflation shows a positive but statistically insignificant effect, suggesting that domestic price increases do not have a strong statistical impact on exports. Meanwhile, the interest rate has a negative and significant effect, indicating that rising interest rates can hinder export activity by increasing business financing costs.